2013
DOI: 10.26719/2013.19.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Possible health effects of liquefied petroleum gas on workers at filling and distribution stations of Gaza governorates

Abstract: Liquefied petroleum gas (LPG) is widely used in the Gaza Strip for domestic purposes, in agriculture and industry and, illegally, in cars. This study aimed to identify possible health effects on workers exposed to LPG in Gaza governorates. Data were collected by a questionnaire interview, and haematological and biochemical analyses of venous blood samples were made from 30 workers at filling and distribution stations and 30 apparently healthy controls. Statistically significant differences were found in all se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…Sirdah et al [190] also found significantly more complaints of eye itches, redness, and pain among workers at liquefied petroleum gas stations in the Gaza governorate. Therefore, gasoline station workers may be exposed to a higher risk of visual impairment.…”
Section: Ocular Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Sirdah et al [190] also found significantly more complaints of eye itches, redness, and pain among workers at liquefied petroleum gas stations in the Gaza governorate. Therefore, gasoline station workers may be exposed to a higher risk of visual impairment.…”
Section: Ocular Effectsmentioning
confidence: 96%
“…Sirdah et al [190] reported a higher prevalence of skin redness, rashes, and itching that gasoline, either on its own or mixed with certain nonimmunotoxic additives (e.g., t-amyl methyl ether (TAME), and t-butyl alcohol (TBA)) did not adversely affect the humoral immune response of the test animals; however, when mixed with some immunotoxic agents, such as ethanol (EtOH) [173,174], ethyl t-butyl ether (ETBE), and diisopropyl ether (DIPE), suppressed humoral responses. Gasoline immunotoxicity may indeed be influenced by additive immunotoxins, particularly when present at a high concentration or upon prolonged exposure.…”
Section: Dermatologic Effectsmentioning
confidence: 99%
“…According to a study on LPG workers, it was determined that red blood cell count, hemoglobin level, platelet count, kidney function tests (urea, uric acid, and creatinine), and liver function tests (AST, ALT) are all significantly higher in the LPG group compared to the control group. It was found that self-reported health-related complaints among LPG workers were higher compared to healthy controls [ 11 ]. Fortunately, there were no pathologic findings in the hematologic and biochemical tests of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…LPG can cause frostbite and irritation if contact with eyes or skin. Exposure to high amounts of LPG in the environment, can reduce the amount of oxygen in the air, causing weakness in humans around with symptoms of headache, dizziness, nausea and vomiting [16]. Minimum oxygen levels in air are 19.5% by volume.…”
Section: Theorymentioning
confidence: 99%
“…Long-term gas exposure can cause thirst, lethargy, fatigue, weight loss, central nervous system damage, nosebleeds, rhinitis, halitosis, ulceration of the mouth and nose, conjunctivitis, anorexia [18]. Publications in 1996 and 2004 also reported the occurrence of sudden deaths due to LPG inhalation, which shows that the liver and kidneys were among the major organs where high concentrations of LPG accumulated [16]. Two mechanisms to be considered for death after LPG inhalation are asphyxia and depress central nervous system [19].…”
Section: Theorymentioning
confidence: 99%